Developing and validating a preoperative risk score to predict 90‐day mortality after liver resection. Issue 4 (13th January 2019) - Dasari, Bobby V. M.; Hodson, James; Sutcliffe, Robert P.; Marudanayagam, Ravi; Roberts, Keith J.; Abradelo, Manuel; Muiesan, Paolo; Mirza, Darius F.; Isaac, John
Abstract : Background: Hepatobiliary surgeons continue to expand the pool of patients undergoing liver resection using combinations of surgical and interventional procedures with chemotherapy. Improved perioperative care allows for operation on higher risk surgical patients. Postoperative outcomes, including 90‐day mortality that improved over the past decade but still varies across cohorts. This study developed a preoperative risk score, on the basis significant clinical and laboratory variables, to predict 90‐day mortality after hepatectomy. Methods: All patients who underwent hepatectomy between 2011 and 2016 were included. Univariable and multivariable analyses were performed to identify the predictors of postoperative mortality and a risk score was derived and validated. Results: The overall 90‐day mortality rate in the derivation cohort (n = 1269 patients) was 4.0% (N = 51). Increasing patient age ( P  < 0.001), extent of resection ( P  = 0.001), diabetes mellitus ( P  = 0.006), and low preoperative sodium ( P  = 0.012) were predictors of the increased 90‐day mortality in the multivariable analysis. The risk model developed based on these factors had an AUROC of 0.778 ( P  < 0.001) and remained significant in a validation cohort of 788 patients (AUROC: 0.703, P  < 0.001). Conclusion: The proposed preoperative risk score to predict 90‐day mortality after liver resection could be useful for appropriate counseling, optimization, and risk‐adjusted assessment of surgical outcomes.